2021
DOI: 10.1111/jvh.13603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the renal safety of tenofovir disoproxil fumarate in hepatitis B patients without chronic kidney disease

Abstract: The nephrotoxicity of tenofovir disoproxil fumarate (TDF) in chronic hepatitis B (CHB) patients without chronic kidney disease (CKD) remains controversial. We aimed to evaluate nephrotoxicity of TDF in this population. In this hospital‐based cohort study, CHB patients who received either TDF or entecavir (ETV) therapy, and did not have underlying CKD, were retrospectively recruited from January, 2008 to January, 2019. After excluding those with confounding conditions, 257 TDF‐treated patients were matched thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Even in HBV-HIV-coinfected individuals, Labarga et al ., 2009 [26] did not find impairment of renal function when analyzing 154 individuals after 14 months of treatment with TDF. Recently, a meta-analysis [32] corroborated these prior findings by also demonstrating slight declines in mean GFR after treatment with TDF for 18–24 weeks [33–38], with all variations in values being between −2.5 ml/min/1.73 m 2 [32] and −6.87 ml/min/1.73 m 2 [39], except one (−18.7 ml/min/1.73 m 2 ) [33], findings that are similar to our research.…”
Section: Discussionsupporting
confidence: 90%
“…Even in HBV-HIV-coinfected individuals, Labarga et al ., 2009 [26] did not find impairment of renal function when analyzing 154 individuals after 14 months of treatment with TDF. Recently, a meta-analysis [32] corroborated these prior findings by also demonstrating slight declines in mean GFR after treatment with TDF for 18–24 weeks [33–38], with all variations in values being between −2.5 ml/min/1.73 m 2 [32] and −6.87 ml/min/1.73 m 2 [39], except one (−18.7 ml/min/1.73 m 2 ) [33], findings that are similar to our research.…”
Section: Discussionsupporting
confidence: 90%
“…However, some studies (Park et al 2017;Riveiro-Barciela et al 2017) showed that patients receiving TDF and ETV treatment did not show significant differences in eGFR levels during the 24-month observation period. A newly published study by Tsai et al (Tsai et al 2021) showed that TDF and ETV had a similar mean decrease in eGFR at up to 60 months of follow-up (TDF: 10.1ml/min/1.73m 2 , 95% [CI]: 7.4 -12.7; ETV: 8.0ml/min/1.73m 2 , 95% [CI]: 6.4-9.6), indicating that TDF is safe for CHB patients without chronic renal insufficiency. However, it was found that in older adults ≥60 years old receiving TDF treatment, the 5-year cumulative incidence of renal insufficiency was significantly higher (TDF: 34.4%, 95% [CI]: 17.7-59.8; ETV: 15.5%, 95% [CI]: 9.4-25.1).…”
Section: Discussionmentioning
confidence: 99%
“…Then, we reviewed the remaining 86 articles by reading full texts. Sixteen reports (4 prospective cohort studies (Kahraman et al 2022;Koklu et al 2015;Koksal et al 2019;Riveiro-Barciela et al 2017), ten retrospective cohort studies (Centeno et al 2016;Chon et al 2022;Huang et al 2021;Kara et al 2019;Kim et al 2020;Liu et al 2022;Park et al 2017;Tsai et al 2021;Udompap et al 2018;Wei et al 2019), and two cross-sectional studies (Tien et al 2015;Rodríguez-Nóvoa et al 2016)) were considered eligible and included in the meta-analysis.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Safety studies of tenofovir disoproxil fumarate (TDF) in patients without renal impairment as well as in healthy people using HIV pre‐exposure prophylaxis based on TDF and another antiviral are generally reassuring. This good safety profile is a major asset for using TDF as prevention 7–10 . Entecavir and newer drugs such as tenofovir alafenamide have better renal tolerance profiles.…”
mentioning
confidence: 99%
“…This good safety profile is a major asset for using TDF as prevention. [7][8][9][10] Entecavir and newer drugs such as tenofovir alafenamide have better renal tolerance profiles. A cure for chronic hepatitis B infection may be available in the coming years.…”
mentioning
confidence: 99%